2004
DOI: 10.1094/pdis.2004.88.2.220b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Bacterial Canker of Walnut Caused by Brenneria nigrifluens in France

Abstract: Since the summer of 2000, vertical oozing cankers have been observed on trunks and branches of Persian walnut trees (Juglans regia). Cvs. Fernor, Chandler, Mayette, and Hartley were the most frequently affected, but cvs. Lara and Franquette could also be affected. Brenneria nigrifluens (synonym Erwinia nigrifluens) (3) was isolated from diseased trees from 13 orchards and nurseries in southwestern (Aquitaine, Périgord, Charentes, and Quercy), southeastern (Grenoble areas), and western (near Angers) France. Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
2
23
0
4
Order By: Relevance
“…Strains of the pathovar are responsible for walnut blight and VOC, a disease that appeared in French walnut orchards in the early 2000s (56,92). MLST and pathogenicity tests showed that only a few closely related sequence types within the pathovar juglandis clonal complex are able to cause typical VOC symptoms, confirming the previous results of Hajri et al (56) based on fluorescent AFLP (f-AFLP).…”
Section: Discussionsupporting
confidence: 84%
“…Strains of the pathovar are responsible for walnut blight and VOC, a disease that appeared in French walnut orchards in the early 2000s (56,92). MLST and pathogenicity tests showed that only a few closely related sequence types within the pathovar juglandis clonal complex are able to cause typical VOC symptoms, confirming the previous results of Hajri et al (56) based on fluorescent AFLP (f-AFLP).…”
Section: Discussionsupporting
confidence: 84%
“…En Europa B. nigrifluens fue identificado en huertas de nogal de castilla. Posteriormente, la bacteria fue detectada en Francia e Italia en plantas jóvenes y árboles adultos (Saccardi et al, 1998;Morone et al, 1998;Ménard et al, 2004;Nelson y Hudler, 2007;Scortichini, 2008;Abeysekara, 2014;Narayanasamy, 2011). En España B. rubrifaciens ha sido reportada en nogales de castilla y en árboles importados de California (González et al, 2002;Nelson y Hudler, 2007).…”
Section: Palabras Clave Adicionalesunclassified
“…En el nogal de castilla Ménard et al, (2004) comprobaron la patogenicidad de tres cepas, al inocular con 10 8 UFC heridas de ramas de 7 años de edad. La cepa de referencia y agua fueron inoculadas de manera similar como testigos.…”
Section: Pruebas De Patogenicidadunclassified
“…Il patogeno non è nuovo in Italia: descritto per la prima volta su noce nero americano in California (Wilson et al 1957) e segnalato a metà degli anni '90 in Spagna su noce europeo (López et al 1994), fu poi osservato nel nostro Paese proprio in Piemonte (Morone et al 1998) e quasi contemporaneamente in Veneto (Saccardi et al 1998), quindi in Lazio (Scortichini 1999) e in Campania (Carella et al 2003). Comparso poco più tardi in Francia (Ménard et al 2004) e da ultimo in Serbia (Popović et al 2013), le segnalazioni del batterio sono andate intensificandosi nel nostro Paese soprattutto nell'ultimo lustro. Conosciuto in letteratura anglosassone come agente di cancro corticale superficiale (Shallow Bark Canker, SBC) per contrapporlo a Brenneria rubrifaciens (Wilson et al) Hauben et al, agente di cancro corticale profondo (Deep Bark Canker, DBC) allo stato attuale non ancora diffuso in Europa se non in un distretto spagnolo (Gonzá-lez et al 2002), B. nigrifluens rappresenta una minaccia potenziale per la conduzione degli impianti di noce misti e soprattutto in purezza, viste anche le scarse conoscenze sulle condizioni predisponenti alla sindrome e più in generale sulla sua epidemiologia in Italia.…”
unclassified